Measuring Nursing Students' Competency Achievements Based on Outcome-Based Education - Rossa, M. Adila; Darmojo, Hardjito S; Siswosuharjo, Partono (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
Measuring nursing students' competency achievement is a crucial component in ensuring the quality of graduates who are ready to practice professionally safely and effectively. The Outcome-Based Education approach emphasizes the achievement of students' actual abilities through alignment of the curriculum, learning process, and a continuous evaluation system. This study aims to explore in-depth the process of measuring nursing students' competency achievement based on Outcome-Based Education from the perspectives of final-year students and clinical supervisors. The study employed a qualitative design with a phenomenological approach. Participants were selected purposively until data saturation was achieved. Data were collected through in-depth interviews, participant observation, and document review, followed by thematic analysis. The results identified five main themes: understanding the concept of Outcome-Based Education, the gradual and continuous process of measuring competency, factors supporting competency achievement, barriers to implementing outcome-based evaluation, and the impact on readiness for professional practice. The outcome-based approach has been shown to improve the integration of theory and practice, improve students' self-confidence, and improve critical thinking skills. However, challenges remain, including variations in assessment standards, limited practice time, the administrative burden of evaluation, and anxiety about competency testing. These findings confirm that measuring competency based on Outcome-Based Education requires standardized instruments, strengthening the capacity of clinical supervisors, and ongoing institutional support